Dinamika dan Karakter Produk Hasil Dekarboksilasi Sabun Hidroksi Pelargonat - Ella Melyna; Tirto Prakoso; Tatang Hernas Soerawidjaja (Jurnal Teknik Kimia dan Lingkungan, 2021)
The development of biofuel have a lot of advantages for national growth, such as, imports reduction of fuel and increasing national energy security and sustainability. Therefore, biofuel production technology for substitution of fuel oil especially gasoline, is very important. One of technology method to produce biogasoline is decarboxylation of pelargonic hydroxy metal soap. Magnesium hydroxy pelargonate [Mg(OH)(OOCC8H17)] can be decarboxylated to produce n-octane [C8H18] and magnesium carbonate [MgCO3] which at temperatures close to 500oC decompose into MgO and CO2. The objectives of this research is to investigate comprehensively the dynamics and character liquid products from decarboxylation of pelargonic hydroxy soap [Mg(OH)OOCC8H17] reaction at temperature range of 250-350oC.